Associations of gestational diabetes and proton density fat fraction of vertebral bone marrow and paraspinal musculature in premenopausal women - Harada, Saori; Gersing, Alexandra S.; Stohldreier, Yannick; Dietrich, Olaf; Lechner, Andreas; Seissler, Jochen; Ferrari, Uta; Pappa, Eleni; Hesse, Nina (Frontiers in Endocrinology, 2024)
Background and Objective:Fat content in bones and muscles, quantified by magnetic resonance imaging (MRI) as a proton density fat fraction (PDFF) value, is an emerging non-invasive biomarker. PDFF has been proposed to indicate bone and metabolic health among postmenopausal women. Premenopausal women with a history of gestational diabetes (GDM) carry increased risk of developing type 2 diabetes, and increased fractures. However, no studies have investigated the associations between a history of GDM and PDFF of bone or of paraspinal musculatures (PSM), composed of autochthonous muscle (AM) and psoas muscle, being responsible for moving and stabilizing the spine. This study aims to investigate whether PDFF of vertebral bone marrow and of PSM are associated with a history of GDM in premenopausal women.Methods:Thirty-seven women (mean age 36.3 ± 3.8 years) 6 to 15 months postpartum with (n=19) and without (n=18) a history of GDM underwent whole body 3T MRI, including a chemical shift encoding-based water-fat separation. PDFF maps were calculated for the vertebral bodies and PSM. The cross-sectional area (CSA) of PSM was obtained. Associations between a history of GDM and PDFF were assessed using multivariable linear and logistic regression models.Results:The PDFF of the vertebral bodies was significantly higher in women with a history of GDM (GDM group) than in women without (thoracic: median 41.55 (interquartile range 32.21-49.48)% vs 31.75 (30.03-34.97)%; p=0.02, lumbar: 47.84 (39.19-57.58)% vs.36.93 (33.36-41.31)%; p=0.02). The results remained significant after adjustment for age and body mass index (BMI) (p=0.01-0.02). The Receiver Operating Characteristic curves showed optimal thoracic and lumbar vertebral PDFF cutoffs at 38.10% and 44.18%, respectively to differentiate GDM (AUC 0.72 and 0.73, respectively, sensitivity 0.58, specificity 0.89). The PDFF of the AM was significantly higher in the GDM group (12.99 (12.18-15.90)% vs 10.83 (9.39-14.71)%; p=0.04) without adjustments, while the CSA was similar between the groups (p=0.34).Conclusion:A history of GDM is significantly associated with a higher PDFF of the vertebral bone marrow, independent of age and BMI. This statistical association between GDM and increased PDFF highlights vertebral bone marrow PDFF as a potential biomarker for the assessment of bone health in premenopausal women at risk of diabetes.